Oral pretreatment with β-lactoglobulin derived peptide and CpG co-encapsulated in PLGA nanoparticles prior to sensitizations attenuates cow’s milk allergy development in mice - Liu, Mengshan; Thijssen, Suzan; Hennink, Wim E.; Garssen, Johan; van Nostrum, Cornelus F.; Willemsen, Linette E. M. (Frontiers in Immunology, 2023)
Cow’s milk allergy is a common food allergy among infants. Improved hygiene conditions and loss of microbial diversity are associated with increased risk of allergy development. The intestinal immune system is essential for oral tolerance induction. In this respect, bacterial CpG DNA is known to drive Th1 and regulatory T-cell (Treg) development via Toll-Like-Receptor 9 (TLR-9) signaling, skewing away from the allergic Th2 phenotype. We aimed to induce allergen specific tolerance via oral delivery of poly (lactic-co-glycolic acid) nanoparticles (NP) co-encapsulated with a selected β-lactoglobulin derived peptide (BLG-Pep) and TLR-9 ligand CpG oligodeoxynucleotide (CpG). In vivo, 3-4-week-old female C3H/HeOuJ mice housed in individually ventilated cages received 6-consecutive-daily gavages of either PBS, whey, BLG-Pep/NP, CpG/NP, a mixture of BLG-Pep/NP plus CpG/NP or co-encapsulated BLG-Pep+CpG/NP, before 5-weekly oral sensitizations with whey plus cholera toxin (CT) or only CT (sham) and were challenged with whey 5 days after the last sensitization. The co-encapsulated BLG-Pep+CpG/NP pretreatment, but not BLG-Pep/NP, CpG/NP or the mixture of BLG-Pep/NP plus CpG/NP, prevented the whey-induced allergic skin reactivity and prevented rise in serum BLG-specific IgE compared to whey-sensitized mice. Importantly, co-encapsulated BLG-Pep+CpG/NP pretreatment reduced dendritic cell (DC) activation and lowered the frequencies of PD-L1+ DC in the mesenteric lymph nodes compared to whey-sensitized mice. By contrast, co-encapsulated BLG-Pep+CpG/NP pretreatment increased the frequency of splenic PD-L1+ DC compared to the BLG-Pep/NP plus CpG/NP recipients, in association with lower Th2 development and increased Treg/Th2 and Th1/Th2 ratios in the spleen. Oral administration of PLGA NP co-encapsulated with BLG-Pep and CpG prevented rise in serum BLG-specific IgE and symptom development while lowering splenic Th2 cell frequency in these mice which were kept under strict hygienic conditions.